Metoda regresji w szacowaniu braków danych - Białowąs, Sylwester (Regression Method in the Assessment of the Lock of Data, 2006)
The text describes a problem of missing values in the data sets used for statistical analysis. Consequences of working with data sets with missing values as well as some of the most popular methods of data imputation are presented together with an example comparing two simplest methods of imputation of missing values - the average vs. The linear regression. In line with the theory, better results were achieved using the linear regression for data imputation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 562-567